Determination of biotin in Antarctic krill (Euphausia superba) by high‐performance TLC with different post‐chromatographic derivatizations. Issue 16 (19th July 2013) - Teo, Peishan; Liu, Daicheng
<x xml:space="preserve">Abstract</x> A new efficient method was developed to detect biotin in Antarctic krill by Vis‐absorbance detection. DMF was used after chloroform pretreatment to extract biotin and two chromogenic methods were developed. The development system consisted of dichloromethane/dimethylcarbinol/methanol/glacial acetic acid (3:3:2:0.015, v/v/v/v). Samples were separated on precoated silica gel GF254 high‐performance TLC plates. Densitometric analysis of biotin was carried out in the absorbance mode at 400 and 530 nm. The biotin content was determined to be 1.0948 ± 0.0097 and 1.1212 ± 0.0155 mg/g in Antarctic krill with the two chromogenic methods, which had no significant difference.